Available energy analysis of a petroleum refinery - Erkan, Deniz. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
The aim of this thesis is to examine the concept of available energy (availability) as applied to a petroleum refinery. For this purpose two different parts of the refinery were investigated. The first part, namely the plant 5 of İPRAŞ Refinery, deals mainly with separation and heat transfer processes. The second part, namely the Plant 6 of İPRAŞ Refinery, deals mainly with chemical reaction processes. The data needed in the calculation for Plant 5 were supplied by İPRAŞ. However, since Plant 6 involves chemical reactions and in chemically reacting systems standard chemical availabilities are needed and these standard chemical availabilities had to be simply estimated because of the uncertain structure of fractions. Therefore, the availability calculations carried out for Plant·6 are quite approximate and they are preliminary in nature. In addition, an availability analysis was made for each equipment of Plant 5 to investigate vlhere the availability losses occurred. The majority of process availability losses are in the furnaces, heat exchangers before desalters and in the air and water coolers. The availability loss of the overall process was also calculated for Plant 5 bv an overall balance. For·Plant 6, on the other hand, the availability calculations were made approximately only for the overall process .because of thelack of necessary data. In addition, an availability efficiency, which is also called Second Law efficiency in literature, was defined and it was reduced to suitable forms for different equipment.
Keywords: Petroleum refineries.; Petroleum -- Refining.; Power resources.; Energy consumption.